EFFICIENT AND ECO-FRIENDLY MANAGEMENT OF BIODEGRADABLE MUNICIPAL SOLID WASTE (MSW) USING NATURALLY AERATED WINDROW COMPOSTING TECHNIQUE IN DISTRICT LAHORE PAKISTAN - Naveed; Tanveer; Abdul Nasir; Asma; Chaudhary; Muhammad Qamar; Zillay (Earth Sciences Pakistan, 2017)
In urban areas, management of solid waste is a big and serious issue because of high amount of waste generated from different sources (industries, domestic etc.). In Lahore solid waste generated daily is about 5000 ton comprising of around 60% biodegradable and 40% non-biodegradable waste. About 70% of waste is collected which is then disposed of in unmonitored dumping sites. It causes severe environmental problems. The present study is for minimizing the solid waste being collected. Composting technique was adopted from Municipal solid waste and garden waste. The aerated composting technique made results more efficient by using an effective microbe’s solution which acts as an activator to enhance microbial activity and reduced the composting period. The results demonstrated that compost was good in organic content 25% and carbon-nitrogen ratio 26:1. It was planned to convert organic waste into compost thus substantially reducing the MSW loads being generated in Lahore.